2020
DOI: 10.1136/annrheumdis-2020-eular.5716
|View full text |Cite
|
Sign up to set email alerts
|

Thu0013 integrated Analysis of Synovial Single Cell Rna Sequencing Data Deepens the Current Knowledge of Synovial Pathology in Arthritis

Abstract: Background:The heterogeneity of synovial tissues from patients with arthritis could contribute to the interpatient variability in disease course, prognosis and treatment response. Single-cell RNA sequencing (scRNA-seq) permits in-depth analysis of tissue heterogeneity, which could facilitate drug discovery and patient stratification for precision medicine.Objectives:To construct a comprehensive landscape of synovial cell types and molecular pathways in arthritis by integrating our and published scRNA-seq data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…And the multinomial logistic regression showed that, in addition to age and previous injury in target knee, the GG genotype (p=0,032) emerged as a potential risk factor for the RPOA when compared with non-rapid progressors (Table 2). [1][2][3] was performed using Seurat protocol 4 with correction for batch effects and filtering low-quality cells. Functional enrichment analysis of marker genes in clusters was done with STRING Protein-Protein networks.…”
mentioning
confidence: 99%
“…And the multinomial logistic regression showed that, in addition to age and previous injury in target knee, the GG genotype (p=0,032) emerged as a potential risk factor for the RPOA when compared with non-rapid progressors (Table 2). [1][2][3] was performed using Seurat protocol 4 with correction for batch effects and filtering low-quality cells. Functional enrichment analysis of marker genes in clusters was done with STRING Protein-Protein networks.…”
mentioning
confidence: 99%